The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms23147844
|View full text |Cite
|
Sign up to set email alerts
|

Are We Ready to Implement Molecular Subtyping of Bladder Cancer in Clinical Practice? Part 2: Subtypes and Divergent Differentiation

Abstract: Following several attempts to achieve a molecular stratification of bladder cancer (BC) over the last decade, a “consensus” classification has been recently developed to provide a common base for the molecular classification of bladder cancer (BC), encompassing a six-cluster scheme with distinct prognostic and predictive characteristics. In order to implement molecular subtyping (MS) as a risk stratification tool in routine practice, immunohistochemistry (IHC) has been explored as a readily accessible, relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 130 publications
1
8
0
Order By: Relevance
“…HER2 alterations have been extensively studied in MPCs [ 71 , 72 , 73 ], with rates of overexpression and amplification in up to 75% and 42% of cases, respectively [ 74 , 75 ], supporting the classification of MPCs as luminal tumors [ 7 , 71 ]. Two studies comparing stage-matched MPC to conventional BC reported higher amplification rates in the first group (12% and 15% vs. 6% and 9%, respectively) [ 70 , 73 ].…”
Section: Her2 In Divergent Differentiation and Histological Subtypes ...mentioning
confidence: 99%
See 2 more Smart Citations
“…HER2 alterations have been extensively studied in MPCs [ 71 , 72 , 73 ], with rates of overexpression and amplification in up to 75% and 42% of cases, respectively [ 74 , 75 ], supporting the classification of MPCs as luminal tumors [ 7 , 71 ]. Two studies comparing stage-matched MPC to conventional BC reported higher amplification rates in the first group (12% and 15% vs. 6% and 9%, respectively) [ 70 , 73 ].…”
Section: Her2 In Divergent Differentiation and Histological Subtypes ...mentioning
confidence: 99%
“…The biological and clinical heterogeneity of BC has led several researchers to develop classification schemes able to mirror this variability and translate it into distinct subtypes according to their mRNA expression profiles in the last decade. The next steps were to combine these findings into a consensus classification and to implement such molecular subtyping as a risk-stratification tool in routine practice, using IHC in order to assess subtype-specific biomarkers at the protein level [ 7 , 8 ].…”
Section: Her2 and Bc Molecular Subtypesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, several studies based on transcriptional analysis have resulted in different attempts at molecular subtyping of MIBCs, all of them sharing the top-level distinction into luminal and basal tumor types, as highlighted by a recent consensus classification [ 6 , 7 ], with each subtype being associated with peculiar clinical features as well as variable sensitivity to treatments. Immunohistochemical (IHC) antibodies have been described as effective surrogate markers for both luminal (CK20, GATA3) and basal (high-molecular-weight cytokeratins, such as CK5/6 and CK14) tumors, in order to translate research findings into routine clinical practice [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter has activated PPAR-γ and FGFR3 mutations, with enriched epithelial markers, and a good clinical prognosis, whereas basal tumors are associated with EGFR regulon activity, usually present at an advanced stage, and have the worst clinical prognosis [ 10 ]; nevertheless, they seem to be more sensitive to neoadjuvant cisplatin-based chemotherapy than luminal MIBCs [ 11 , 12 ]. The routine performance of molecular analysis in current practice is undermined by technical and economic issues; thus, immunohistochemical (IHC) surrogates for molecular profiling have been identified by validating the consistency between mRNA expression profiles and the expression of immunohistochemical markers [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%